PERAN KONSELING SEBAYA DALAM MENINGKATKAN RESILIENSI PSIKOLOGIS WARGA BINAAN DI LEMBAGA PEMASYARAKATAN KELAS IIA PURWOKERTO - Robbani, Achmad Ariq; Turhamun, (Realita : Jurnal Bimbingan dan Konseling, 2026)
Correctional institutions do not merely function as places for serving sentences, but also as spaces for rehabilitation to enable inmates to reintegrate socially after completing their imprisonment. However, in reality, young inmates are vulnerable to experiencing significant psychological distress, including loss of freedom, social stigma, separation from family, and uncertainty about the future. These conditions often lead to decreased life motivation, feelings of hopelessness, and loss of life purpose. Such circumstances may reduce psychological resilience, defined as an individual’s ability to recover, endure, and adapt positively in the face of stress and adversity. This study aims to examine the role of peer counseling in enhancing the psychological resilience of inmates at Class IIA Purwokerto Correctional Institution. This research employed a qualitative method with a case study approach. The participants consisted of young adult inmates and internship staff involved in the implementation of peer counseling. Data were collected through participatory observation and documentation and analyzed using thematic analysis. The findings indicate that prior to participating in peer counseling, inmates demonstrated low motivation, anxiety about the future, and a sense of hopelessness. After engaging in peer counseling sessions, participants showed increased life motivation, renewed hope and future aspirations, improved emotional regulation, and enhanced self-confidence. Emotional closeness and shared experiences were identified as key factors contributing to the program’s effectiveness. Therefore, peer counseling plays a significant role in strengthening inmates’ psychological resilience and can serve as an effective rehabilitative strategy to support their social reintegration.